Synthesis, crystal structure, hirshfeld study, DFT analysis, molecular docking study, antimicrobial activity of β-enaminonitrile bearing 1H-pyran - Al-Anood M. Al-Dies; Fawzia F. Alblewi; Rawda M. Okasha; Mosa H. Alsehli; Rita M. A. Borik; Saleh Ihmaid; Abd El-Galil E. Amr; Hazem A. Ghabbour; Ahmed A. Elhenawy; Ahmed M. El-Agrody (Discover Applied Sciences)
Abstract 3-Amino-1-(3,4-dimethoxyphenyl)-8-methoxy-1H-benzo[f]chromene-2-carbonitrile (3-ABC, 4) was prepared and affirmed through the spectral data and single crystal X-rays diffraction. The molecule spatial attributes were revealed by the three-dimensional Hirshfeld surface, which is validated by comprehensive statistical evaluations. The key interactions that contribute to the crystal's stability and properties, such as π–π stacking and H⋯X contacts, were highlighted. The dominant forces in the crystal were explained by energy framework calculations and density functional theory analyses, which also show the geometric optimization aspects and molecular reactivity indicators. The focus is on the investigation of frontier molecular orbitals, aromaticity, and π–π stacking abilities. The research concluded by identifying electron density distributions, aromatic features, and possible reactivity sites, offering a complete picture of the compound's structural and electronic landscape. Compound 4 was screened for its antimicrobial capability against three Gram-positive, three Gram-negative bacteria, and three fungi, utilizing the reference antibiotic drug Ampicillin, Gentamycin, and Ketoconazole. Compound 4 exhibited favorable antimicrobial activities that were lower/resembled the reference antimicrobial agents with an IZ range of 15–31 mm. In addition, MIC, MBC, and MFC were assessed and screened for the target molecule 4, unveiling its revealing antimicrobial activities. Lastly, the molecular docking evaluation was implemented for the molecules interaction with the DHFR protein. The compounds exhibit significant interactions with the EGFR protein's active site.